Pedagogical Compentence of Mathematics Education Lectures Using LMS (Learning Management System) Moodle in The Era Covid-19 - Suriyah, Puput; Zainudin, M.; Yektiana, Suen (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2021)
This study aimed to investigate to what extent the mathematics education lectures’ pedagogical competence using LMS Moodle in the era covid-19. The researchers employed a case study research design and the participants comprised three mathematics education lecturess who used LMS Moodle IKIP PGRI Bojonegoro. As well, to collect the data, observation, questionnaire, and fieldnotes were used based on the teacher's perspective. The responses were then to be interpreted into percentages and analysed descriptively. There were three main phases to analyse the data, namely data reduction, data display, and conclusion drawing and verification. Moreover, triangulation was applied to validate and verify the data collected. The results of this study indicated that the mathematics education lectures' pedagogical competence was good as a whole of the seventh aspects discussed.